Healthcare utilization and outcomes of patients discharged to skilled nursing facilities on parenteral antimicrobial therapy - Madeline Langenstroer; Christopher Crnich; Sally A. Jolles; Jon P. Furuno; Brie N. Noble; Rosemary C. Bailey (Antimicrobial Stewardship & Healthcare Epidemiology)
Hospitalized patients are commonly discharged to skilled nursing facilities (SNFs) on outpatient parenteral antimicrobial therapy (OPAT). In this study, 101 patients discharged to a SNF on OPAT required considerable post-hospital care coordination and experienced high readmission and mortality rates within 90 days, contributing to literature characterizing OPAT patients in other settings.